Directorial treatment of the vision of the show between two different places in contemporary Iraqi theater performances (Al-Academy, 2025)
The place is considered the incubating and assumed environment according to the directorial imagination and a product of the artistic, cultural, cognitive and methodological awareness of the mechanisms of the directing craft, which carries a strategy and possesses solutions to the obstacles and variables of the theatrical presentation. Therefore, the researcher intended to study these directing variables for the alternative locations with the finest topographical details of the directorial vision and its operations in the alternative locations as he reviewed the concepts. The philosophical, social, economic and political aspects of the alternative place and the difference between the original place and the alternative place on which all studies and research are based because of their intellectual importance as basic references. The research was divided into an introduction and four chapters.